Genetics of Tinnitus: Time to Biobank Phantom Sounds - Cederroth, Christopher R.; Kähler, Anna K.; Sullivan, Patrick F.; Lopez-Escamez, Jose A. (Frontiers in Genetics, 2017)
Tinnitus is a common phantom sensation resulting most often from sensory deprivation, and for which little knowledge on the molecular mechanisms exist. While the existing evidence for a genetic influence on the condition has been until now sparse and underpowered, recent data suggest that specific forms of tinnitus have a strong genetic component revealing that not all tinnitus percepts are alike, at least in how they are genetically driven. These new findings pave the way for a better understanding on how phantom sensations are molecularly driven and call for international biobanking efforts.